2021
DOI: 10.1186/s43019-021-00110-6
|View full text |Cite
|
Sign up to set email alerts
|

Management of mucoid degeneration of the anterior cruciate ligament: a systematic review

Abstract: Purpose The purpose of this study was to investigate the outcomes of management of mucoid degeneration of the anterior cruciate ligament (MDACL) by performing a systematic review of methods of treatment that have been reported. Methods A systematic literature search in the databases MEDLINE, Embase, Google Scholar, Cochrane, ISI web of science and Scopus was performed through July 2020 by three independent reviewers. The review was performed accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…Corroborating these findings were the improvements and the final PROMs of both the groups which corresponded with the findings of the literature review by Sweed et al on nine studies [8]. While both the groups showed improvements in the functional scores post-surgery, which could be attributed to the UKA primarily, the finding that patients in whom debulking was done had better mean IKDC and mean KSS at 2 years follow-up confirmed the study hypothesis that debulking improves the long-term outcome in patients with MD-ACL undergoing UKA.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Corroborating these findings were the improvements and the final PROMs of both the groups which corresponded with the findings of the literature review by Sweed et al on nine studies [8]. While both the groups showed improvements in the functional scores post-surgery, which could be attributed to the UKA primarily, the finding that patients in whom debulking was done had better mean IKDC and mean KSS at 2 years follow-up confirmed the study hypothesis that debulking improves the long-term outcome in patients with MD-ACL undergoing UKA.…”
Section: Discussionsupporting
confidence: 88%
“…This study showed that the patients who underwent debulking had statistically superior knee function, lesser rest pain and greater satisfaction rates at 2 years of follow-up compared with those in whom MD-ACL was not debulked. Various techniques have been proposed for the debulking of MD-ACL including arthroscopic debridement using shaver or radiofrequency ablation, with or without notchplasty, that have shown to give good clinical results [ 8 , 19 ]. The demographic distribution of study population with respect to the mean age, gender distribution and the side affected was similar to the recent studies done on the MD-ACL as a standalone entity [ 2 , 3 , 5 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations